Painleve analysis, Auto-Backlund transformation and new exact solutions for improved modied KdV equation - El-Kalaawy, Omar H.; Aldenari, R. B. (International Journal of Applied Mathematical Research, 2014)
Improved modied Korteweg-de Vries (IMKdV) equation is shown to be non-integrable using Painleve analysis. Exact travelling wave solutions are obtained using auto-Backlund transformation and Linearized transformation. Keywords: IMKdV equation; Painleve analysis; extended homogeneous balance method, auto-Backlund transformation, Linearized transformation, and exact solutions.